THE EFFECTIVENESS OF EXTERNAL AUDIT IN ENHANCING PERFORMANCE OVERSIGHT OF INVESTMENT PROJECTS AND ITS IMPACT ON ACHIEVING TRANSPARENCY AND ACCOUNTABILITY IN THE PUBLIC BUDGET - Assistant Professor Dr Saddam Catea Hashim Fatimah Oday Qasim (Scholars Digest Publishing, 2024)
This research aims to analyze the effectiveness of external audit in enhancing performance oversight of investment projects. The research is based on a theoretical analysis and a field study that included a careful review of secondary sources related to performance monitoring and its impact on monitoring the completion of investment projects in the general budget. A questionnaire survey was conducted for a sample of government units whose budget includes financial allocations for investment projects to obtain their opinions and experiences with regard to monitoring performance and its impact. The research concluded that effective external audit directly enhances confidence among the parties concerned, including investors, donors, and citizens. This trust is built on ensuring that funds allocated to investment projects are managed efficiently and in accordance with international standards, which enhances accountability and transparency in the public budget. The most important recommendations were: In order to achieve comprehensive oversight of investment projects, cooperation must be strengthened between external and internal auditing and other regulatory bodies. Linking these bodies ensures the integration of oversight efforts, enhances the effectiveness of financial oversight, and reduces gaps that may lead to corruption or mismanagement. The research results contribute to a deeper understanding of the importance of performance oversight of investment projects and enhancing their financial performance.
Keywords: external audit, performance control, general budget Transparency and accountability.